Doenças de suínos - Brum, Juliana Sperotto (2013)
This doctoral thesis involved the study of diseases in pigs, including the description of a case of granulocytic sarcoma and outbreaks of eosinophilic salt poisoning. The study of the characteristics and frequency of disease in swine population in the region covered by the Laboratório de Patologia Veterinária (LPV), Universidade Federal de Santa Maria (UFSM) was conducted through a retrospective study of all autopsy diagnoses. Five hundre and sity four with conclusive diagnoses were set apart. The pig population in the region covered by the study is predominantly family and diagnosed diseases reflect this reality. The infectious and parasitic diseases were the most prevalent [384 (68.1%)], followed, in descending order, nutritional and metabolic diseases [64 (11.,3%)], poisoning and toxi-infections [33(5,8%)] and developmental disorders [17(3.1%)]. Other changes to various etiologies, especially trauma, were cause of death in just over 11% of the protocols examined. Bacterial diseases were responsible for more than half of the causes of death or reason for euthanasia of animals studied, pointing to the influence of management, environmental and nutritional regional husbundry . The main disease diagnosed in pigs in the region covered by the study is the edema disease and along with other forms of infection by Escherichia coli is responsible for 23% of deaths of viral diseases and cancer are not major causes of death in pigs in the region studied. Nutritional hepatose and aflatoxicosis are important diseases in the region and and there cuasation are mainly linked to nutritional management. For description of eosinophilic granulocytic sarcoma, a set of techniques (cytology, histology, histochemistry and immunohistochemistry)were used and which proved to be essential for the confirmation of macroscopic tentive diagnosis. Salt poisoning is a condition recognized in pigs as far back as the first half of the last century and still remains as an important cause of mortality; the large amount of salt accumulated in the body in cases of poisoning can be demonstrated by determination of sodium ion in the liver, muscle, CSF, serum and aqueous humor, and these are acillary data to confirm the diagnosis. Pigs affected by salt poisoning have eosinopenia due to severe meningoencephalitis and infiltration of eosinophils in tissues, acute neuronal necrosis which develops into deeplaminar cortical necrosis as the clinical progresses.